Information requirement for efficient decentralized screening - Saara Hämäläinen (Helsinki Graduate School of Economics, 2024)
We establish new efficiency results for decentralized markets with quality uncertainty. Buyers encounter a succession of passing trade opportunities and related asset information, allowing them to screen the quality of assets by conditioning pricing on informative signals. We link key equilibrium properties with the intensity of screening. This innovative approach delivers conditions under which efficient equilibria exist, characterizes efficient and inefficient equilibria in terms of asset screening and trade dynamics, and presents a new measure for the information required for efficient trade and asset screening. Trade dynamics may manifest as either standard or reversed.
Keywords: D82; D83; 330; decentralized lemons market; screening; buyer signals; trade dynamics; efficient equilibrium; equilibrium existence